Zingiberis rhizoma-based carbon dots alter serum oestradiol and follicle-stimulating hormone levels in female mice - Yumin Chen; Xue Bai; Ying Zhang; Yafang Zhao; Huagen Ma; Yunbo Yang; Meijun Wang; Yinghui Guo; Xiaopeng Li; Tong Wu; Yue Zhang; Hui Kong; et al. (Artificial Cells, Nanomedicine, and Biotechnology, 2024)
Chinese herbs contain substances that regulate female hormones. Our study confirmed that Zingiberis rhizoma carbonisata contains Zingiberis rhizoma-based carbon dots (ZR-CDs), which exert regulatory effects on serum oestradiol and FSH in mice and show impacts on endometrial growth and follicular development that potentially affect the ability of female fertility. ZR-CDs were characterized to clarify the microstructure, optical features, and functional group characteristics. It shows that ZR-CDs are spherical carbon nanostructures ranging from 0.97 to 2.3 nm in diameter, with fluorescent properties and a surface rich in functional groups. We further investigated the impact of ZR-CDs on oestradiol and FSH in serum, growth, and the development of ovarian and uterine using normal female mice and exogenous oestradiol intervention model. It was observed that ZR-CDs accelerated oestrogen metabolism and attenuated oestradiol-induced endometrial hyperplasia. Simultaneously, ZR-CDs triggered an increase in FSH, even in the presence of high-serum oestradiol that inhibits FSH secretion. Our findings suggest that ZR-CDs could be a potential therapeutic treatment for anovulatory menstruation.